1990
DOI: 10.3109/14017439009098074
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative Effect of Methylprednisolone Given During Lung Surgery on Plasma Concentrations of C3a and C5a

Abstract: Methylprednisolone or saline (placebo) solution was infused intravenously in 28 patients undergoing elective lobectomy for lung cancer. The state of the complement system during and after surgery and the effects of methylprednisolone on biologically active products of complement were studied by measurements of plasma C3a and C5a anaphylatoxins and leukocyte counts in peripheral blood perioperatively. In the placebo group plasma concentrations of C3a were significantly increased on postoperative days 1 and 2, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

1992
1992
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 22 publications
2
10
0
Order By: Relevance
“…In the current study, we found that the basal values before induction of anaesthesia were comparable to those of adults reported by many researchers (Heideman, Keijser & Gelin 1978;Hallgren, Samuelsson & Modig 1987;Bengtsson et al 1987;Mikawa et al 1990). Activation of the complement system, which is associated with the consumption of serum complement components and the liberation of complement split products, can be determined by measuring the presence of C3a and C5a.…”
Section: Discussionsupporting
confidence: 90%
“…In the current study, we found that the basal values before induction of anaesthesia were comparable to those of adults reported by many researchers (Heideman, Keijser & Gelin 1978;Hallgren, Samuelsson & Modig 1987;Bengtsson et al 1987;Mikawa et al 1990). Activation of the complement system, which is associated with the consumption of serum complement components and the liberation of complement split products, can be determined by measuring the presence of C3a and C5a.…”
Section: Discussionsupporting
confidence: 90%
“…Miyano et al reported that the C3a activation system seemed to be well developed even before week 25 of gestation (14). In the current study, basal values in neonates before induction of anaesthesia were comparable to those demonstrated in adults by many researchers (2,(15)(16)(17). C3 is the common meeting point of the two pathways: the classical and the alternative.…”
Section: Discussionsupporting
confidence: 87%
“…In comparison, our cohort included patients with new‐onset and relapsing disease who may have received immunosuppressive treatment (except rituximab or plasma exchange) at the time of sample procurement. There is evidence that glucocorticoids quickly reduce complement activation . In our cohort, 26% of patients with active disease were receiving glucocorticoids and 48% were receiving steroid‐sparing immunosuppressants when the sample was obtained.…”
Section: Discussionmentioning
confidence: 94%